(untitled) (Zeszyty Naukowe Wydziału Nauk Ekonomicznych, 2021)
Monetary Union has caused a full harmonisation of the financial policy. Country’s accession to the Monetary Union means that it needs to conduct its economic and fiscal policy complying with the public finance’s discipline. In addition, it is a meaningful factor of the country’s economic growth